Java Leaders: Raden Adipati Cakranagara I in the Babad Bagelen Social Psychology Study - Fahri Setyo Utomo; Sahid Teguh Widodo (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
AbstractJavanese script is an ancient manuscript of ancestral cultural heritage in the form of handwriting which stores various expressions of thoughts, feelings, and results of past cultures. The contents of the diary text of the Babad Bagelen manuscript tell about the leading figure of the first Purwareja regent who was formerly known as the Bagelen area, namely Raden Adipati Cakranagara 1. The colonial era was full of pressure and policies that harmed the natives. This leadership attitude is in the manuscript of Babad Bagelen with the study of Social Psychology by David G. Myers. The presentation of the results of this study was carried out by analyzing the leadership attitude of Raden Adipati Cakranagara 1 which includes (1) Caring for others, (2) Reminding others, (3) Serving others, (4) Giving gifts, (5) Distributing good invitation quotes. The above data written in the Babad Bagelen manuscript shows the leadership attitude of Raden Adipati Cakranagara when he became Regent in Purwareja (Bagelen). The attitude studied through the Social Psychology approach is very suitable for revealing the problems writtenKeywords: Babad Bagelen, Raden Adipati Cakranagara 1, Social Psychology, David G. Myers